Studi Kasus Koperasi Desa Merah Putih: Dari Siapa, Oleh Siapa, Untuk Siapa ? - Syafril Syafril; Ferli Erwansyah; Andi Makkulawu Panyiwi Kessi; Muhammad Fahmi; Neti Rosiana Fadilah (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
This study aims to describe the formation of the Red and White Village Cooperative, by whom, and for whom, in accordance with the basic principles of cooperatives. This research is a descriptive qualitative study, as recommended in social research to understand organizational phenomena in depth. The case study method is used in this study, a qualitative research approach that examines a specific phenomenon or unit (individual, group, or event) in depth, detail, and holistically within a real-life context. This method focuses on answering the questions of why and how something occurs. Data collection techniques were conducted through searching national and international journal databases, cooperative regulatory documents, and publications from related institutions, following the practice of literature-based qualitative research commonly used in organizational and public policy studies. The results of the study indicate fundamental differences between the basic principles of cooperatives currently used and the basic principles of the Red and White Village Cooperative. The Red and White Village Cooperative originated from the government, through government channels, and for the general public who need the services of the Red and White Village Cooperative. The Red and White Village Cooperative was established as a government project using government funds.